Performance Appraisal Practices in the Leading Multinational Companies of Bangladesh - Dewan Afrida Hamid (STIM LASHARAN JAYA MAKASSAR, 2023)
This article enquires the status quo of performance appraisal scenario within the leading multinational companies at work in Bangladesh. To this end, seven top-ranking MNCs were selected in respect of a multitude of variables, such as initial motives for PA process, positive outcomes, limitations, human errors, criteria for PA conduction, impact PA process on employee loyalty, the frequency of occurrence, the authorities in charge of PA process, employee training facilities, employee satisfaction with the existing assessment practice, rewarding system and so on. The degree to which these variables work as contributing factors has been put to test through appropriate varieties of statistical measurements. The findings are revolutionary and have been exhibited with detailed information of the sample set. The study then proceeds to address the problems and propose the recommendations on the limitations that have surfaced during the discussion.